100 Inspiring Rafflesians, 1823-2003. - Heng, Tan Guan (World Scientific Publishing Company, 2007)
This enlightening book describes the lives and achievements of eminent Rafflesians from Raffles Institution, Raffles Girls'; School and Raffles Junior College, many of whom have served in the Singapore public and community service in the highest positions. The biographies contain little known facts of interest, which have been embellished with personal anecdotes obtained from those interviewed. The book also represents a brave undertaking by a visually handicapped person, who is himself a Rafflesian. Sample Chapter(s). Foreword (59 KB). Contents: 100 profiles: Benjamin Sheares, Lee Kuan Yew, K.